Pelaksanaan Perlindungan Hukum Konsumen Oleh Jasa Ekspedisi Terhadap Rusak Atau Hilangnya Barang Kiriman Pada PT. Indah Cargo Aek Kanopan - Pasaribu, Indri Yani; Munawir, Zaini; Mina, Revi Fauzi (JUNCTO: Jurnal Ilmiah Hukum, 2023)
Expedition services are one of the services that are much needed by the community to facilitate sending goods between cities and between countries. The method used in this research is the type of Empirical Normative Juridical research and the nature of the research uses descriptive analysis. Research data is collected using field studies by conducting interviews, and literature studies, and analysis is carried out with a statutory approach. The results of this study indicate that the freight forwarding agreement of PT Indah Logistik Cargo Aek Kanopan contains several standard clauses that limit the elements of the substance of the GCPL, especially on the transfer of responsibility for the loss or damage of the shipment and the implementation of legal protection to consumers of expedition services for damaged or lost shipments that have not run optimally due to the authority of the branch office is only limited to receiving reports and then submitting them to the head office which has all the authority regarding consumer loss responsibility.